The implementation of EMI-Heart, a family-tailored early motor intervention in infants with complex congenital heart disease, in practice: a feasibility RCT - Elena Mitteregger; Tineke Dirks; Manuela Theiler; Oliver Kretschmar; Beatrice Latal (Pilot and Feasibility Studies, 2024)
Abstract Background Children with congenital heart disease (CHD) who undergo open-heart surgery are at risk of developmental impairment, including motor delay, which contributes to parental concerns. Additionally, parents experience prolonged stress associated with their child’s disease. There is a lack of early motor interventions in infants with CHD accounting for parental burdens. We developed a family-tailored early motor intervention (EMI-Heart), aiming to promote motor development in infants with CHD and family well-being. The primary aim was to evaluate the feasibility of the study design and the intervention. The secondary aim was to evaluate differences between the intervention and the control group in motor outcomes and family well-being at baseline (3–5 months), post-treatment (6–8 months), and at follow-up (12 months). Method In this single-centre feasibility randomized control trial (RCT), infants with CHD after open-heart surgery without genetic or major neurological comorbidities were randomly allocated to EMI-Heart or the control group (standard of care). EMI-Heart’s key elements promote postural functional activities and encourage parental sensitivity to infants’ motor and behaviour cues. Infants assigned to EMI-Heart received nine sessions of early motor intervention at home, in the hospital, and online for a duration of 3 months by a paediatric physiotherapist. We performed descriptive statistics for feasibility and secondary outcomes. Results The recruitment rate was 59% (10/17), all participating families completed the study (10/10), and the intervention duration was 3.9 months (± 0.54), including nine intervention sessions per family. Median acceptability to parents was 3.9 (1 = not agree–4 = totally agree, Likert scale). The paediatric physiotherapist considered the intervention as feasible. The comparison of motor outcomes did not show differences between groups. However, we detected improved reliable change scores in family well-being outcomes for families of the intervention group compared to the controls. Conclusions Our research indicates that EMI-Heart is a feasible intervention for infants with CHD after open-heart surgery. The intervention was highly acceptable both to parents and to the paediatric physiotherapist. Online treatment sessions offer a valuable alternative to home and hospital visits. This feasibility RCT provides a foundation for a future full trial. Trial registration ClinicalTrials.gov, NCTT04666857. Registered 23.11.2020.